2020
DOI: 10.4168/aair.2020.12.4.653
|View full text |Cite
|
Sign up to set email alerts
|

Altered Mitochondrial Functions and Morphologies in Epithelial Cells Are Associated With Pathogenesis of Chronic Rhinosinusitis With Nasal Polyps

Abstract: Purpose: Chronic rhinosinusitis with nasal polyps (CRSwNP) is a complex inflammatory disease of the nasal and paranasal sinus mucosa. The disease is associated with mitochondrial dysfunction, structural changes in the mitochondria, and reactive oxygen species (ROS) generation. This study investigated whether there are functional and morphological changes in the mitochondria in the epithelial cells of nasal polyps (NPs) and Staphylococcus aureus enterotoxin B (SEB)-stimulated nasal epithelial cells. Methods: In… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
10
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 16 publications
(10 citation statements)
references
References 30 publications
0
10
0
Order By: Relevance
“…Increased metabolism in CRS patients could lead to ROS accumulation, 40 cause the continuous inflammation, and further contribute to pathophysiological dysfunction. 41 Additionally, Another study supported the notion that mitochondrial dysfunction might play a role in the pathogenesis of CRSwNP, 42 impaired mitochondria could activate the inflammatory pathway, consequently increasing the release of cytokines. Arginine, a wellknown substrate for nitric oxide (NO) production, has been linked to cellular metabolism, inflammation, and immune responses.…”
Section: Metabolomics Explored In Crssnp and Crswnpmentioning
confidence: 78%
“…Increased metabolism in CRS patients could lead to ROS accumulation, 40 cause the continuous inflammation, and further contribute to pathophysiological dysfunction. 41 Additionally, Another study supported the notion that mitochondrial dysfunction might play a role in the pathogenesis of CRSwNP, 42 impaired mitochondria could activate the inflammatory pathway, consequently increasing the release of cytokines. Arginine, a wellknown substrate for nitric oxide (NO) production, has been linked to cellular metabolism, inflammation, and immune responses.…”
Section: Metabolomics Explored In Crssnp and Crswnpmentioning
confidence: 78%
“…In addition, damaged mitochondria may activate the inflammasome pathway, resulting in increased cytokine release. Another study reported that mitochondrial dysfunction may be associated with the pathogenesis of CRSwNP 15 …”
Section: Discussionmentioning
confidence: 99%
“…Another study reported that mitochondrial dysfunction may be associated with the pathogenesis of CRSwNP. 15 To the best of our knowledge, this is the first integrated multi-omic analysis combining both proteomic and metabolomic data of CRSwNP patients. Key proteins and metabolites involved in mitochondrial function and metabolism of arginine and alpha-linolenic acid may be new therapeutic targets for CRSwNP.…”
Section: Discussionmentioning
confidence: 99%
“…The signal produced is proportional to the amount of analyte bound. The bands' intensities were analyzed using Quick Spots Image Analysis Software (Western Vision Software, http://www.wvision.com/QuickSpots.html ) 33 .…”
Section: Methodsmentioning
confidence: 99%